An Isolable Silicon Analogue of a Ketone that Contains an Unperturbed Si=O Double Bond. Issue 28 (18th June 2019) - Kobayashi, Ryo; Ishida, Shintaro; Iwamoto, Takeaki
Abstract: Despite tremendous efforts to synthesize isolable compounds with an Si=O bond, silicon analogues of ketones that contain an unperturbed Si=O bond have remained elusive for more than 100 years. Herein, we report the synthesis of an isolable silicon analogue of a ketone that exhibits a three‐coordinate silicon center and an unperturbed Si=O bond, thus representing the first example of a genuine silanone. Most importantly, this silanone does not require coordination by Lewis bases and acids and/or the introduction of electron‐donating groups to stabilize the Si=O bond. The structure and properties of this unperturbed Si=O bond were examined by a single‐crystal X‐ray diffraction analysis, NMR spectroscopy, and theoretical calculations. Bimolecular reactions revealed high electrophilicity on the Si atom and high nucleophilicity on the O atom of this genuine Si=O bond. Abstract : Good to Si you : The first example of a genuine silanone, that is, an isolable silicon analogue of a ketone that contains an unperturbed Si=O bond, was synthesized. The structure and properties of this silanone were examined by a single‐crystal XRD analysis, NMR spectroscopy, and theoretical calculations. Bimolecular reactions revealed high electrophilicity on the Si atom and high nucleophilicity on the O atom of the Si=O bond.